1991
DOI: 10.1002/cne.903070413
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of octopamine in the central nervous system of Limulus polyphemus: A light and electron microscopic study

Abstract: We have determined the distribution and localization of the monoamine octopamine in the prosomal central nervous system of the horseshoe crab, Limulus polyphemus, by light and electron microscopic immunocytochemistry. Sixteen discrete clusters of octopamine-like immunoreactive neurons are situated bilaterally in the tritocerebrum and circumesophageal ring of fused thoracic ganglia. Two pairs of anterior clusters are located laterally in the cheliceral and first pedal ganglia; the remaining six pairs of cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…EM studies based on serial sections (Jia et al, 1993) have suggested that type II boutons contain both elliptical dense-core vesicles and small, clear vesicles thought to contain glutamate (Johansen et al, 1989). In other systems, elliptical dense-core vesicles have also been correlated with the presence of octopamine (Lee and Wyse, 1991). In locusts, dorsal unpaired median neurons that contain octopamine also make neurosecretory endings on skeletal muscle (Hoyle et al, 1980).…”
Section: Neuromuscular Innervationmentioning
confidence: 99%
See 1 more Smart Citation
“…EM studies based on serial sections (Jia et al, 1993) have suggested that type II boutons contain both elliptical dense-core vesicles and small, clear vesicles thought to contain glutamate (Johansen et al, 1989). In other systems, elliptical dense-core vesicles have also been correlated with the presence of octopamine (Lee and Wyse, 1991). In locusts, dorsal unpaired median neurons that contain octopamine also make neurosecretory endings on skeletal muscle (Hoyle et al, 1980).…”
Section: Neuromuscular Innervationmentioning
confidence: 99%
“…In Limulus, a role of octopamine in regulating visual sensitivity has been documented (Kass and Barlow, 1984), and, recently, OA-IRy has been observed in efferent fibers in the lateral optic nerves (Lee and Wyse, 1991).…”
mentioning
confidence: 99%
“…Infrequently, insulin-like-immunoreactive boutons are also found at muscle 13 (Gorczyca et al, 1993). In many animal species dense-core vesicles have been associated with monoamine or peptide-containing vesicles (see for example, Lee and Wyse, 1991). DV terminals also contained small clear vesicles.…”
Section: Ultrastructure Of Synaptic Boutons At Muscles 6 7 12 and mentioning
confidence: 99%
“…OA can also modulate behavioral functions (Livingstone et al 1980;Sombati and Hoyle 1984;Casagrand and Ritzmann 1992). The presence of OA has been shown biochemically in the nervous system of other invertebrates, including gastropods (Walker et al 1972;Guthrie et al 1975;McCaman 1980;Lee and Wyse 1991) and leeches Orchard 1980, 1981;Belanger and Orchard 1986). Moreover, the introduction of highly sensitive anti-OA antibodies (Mons and Geffard 1987;Eckert et al 1992) has allowed the mapping and neuroanatomical characterization of OA-like immunoreactive (OA-LI) neurons in the nervous system of a number of invertebrate species (Konings et al 1988;Eckert et al 1992;Spörhase-Eichmann et al 1992;Stevenson et al 1992;Elekes et al 1993;Gilchrist et al 1995).…”
Section: Introductionmentioning
confidence: 96%